Two new species of Nematoda: Gairleanema pulchra sp. nov. (Tripyloididae) and Axonolaimus dimorphous sp. nov. (Axonolaimidae) from the Yellow Sea, China - Liang, Huixin; Guo, Wen; Wang, Chunming (Zootaxa, 2024)
Two new species of Nematoda, Gairleanema pulchra sp. nov. and Axonolaimus dimorphous sp. nov. are described from Rizhao coast, the Yelllow Sea. Gairleanema pulchra sp. nov. is characterized by six inner labial setae with bulbous swelling, six long outer labial setae and four short cephalic setae in one circle, amphidial fovea oval-shaped, spicules L-shaped with proximal end slightly cephalated, gubernaculum boat shaped with proximal end hooked anteriorly, seven oval-shaped precloacal supplements and tail conico-cylindrical. With the species description here two species are considered valid now in genus Gairleanema. Axonolaimus dimorphous sp. nov. is characterized by four long cephalic setae, amphidial fovea elongated loop in males and loop-shaped in females, spicules arcuated, gubernaculum with dorsal apophysis slightly directed to caudal position and tail conico-cylindrical with caudal setae. With the species description here 34 species are considered valid now in genus Axonolaimus.